2020
DOI: 10.1177/0269215520926227
|View full text |Cite
|
Sign up to set email alerts
|

Can inspiratory muscle training benefit patients after stroke? A systematic review and meta-analysis of randomized controlled trials

Abstract: Objectives: The aim of this study was to investigate the effects of inspiratory muscle training in post-stroke patients and to explore the effective training protocol. Data sources: PubMed/Medline, Web of Science, Scopus, Embase, Cochrane database, China National Knowledge Infrastructure, and China Science Periodical Database were searched through April 2020. Review methods: Trials examining effects of inspiratory muscle training on pulmonary function, cardiopulmonary endurance, pulmonary infection incidence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Twelve systematic reviews were carried out on a population with DPOC [ 13 , 15 , 16 , 21 , 30 , 35 , 40 , 42 , 43 , 51 , 53 , 54 ]. Two systematic reviews were carried out on a population with asthma [ 47 , 49 ], two were carried out on a population with amyotrophic lateral sclerosis [ 19 , 34 ], two were carried out on a population with multiple sclerosis [ 44 , 55 ], two were carried out on a population with Parkinson’s disease [ 11 , 20 ], three were carried out on people who were poststroke [ 12 , 18 , 37 ], one was carried out on a population with pulmonary fibrosis [ 25 ], and three were carried out on a population with lung cancer [ 14 , 26 , 45 ]. Six reviews focused on preoperatory preparation [ 24 ] and postoperatory preparation [ 31 , 33 , 52 , 56 ], and three reviews focused on the respiratory exercises for abdominal surgeries [ 17 , 50 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve systematic reviews were carried out on a population with DPOC [ 13 , 15 , 16 , 21 , 30 , 35 , 40 , 42 , 43 , 51 , 53 , 54 ]. Two systematic reviews were carried out on a population with asthma [ 47 , 49 ], two were carried out on a population with amyotrophic lateral sclerosis [ 19 , 34 ], two were carried out on a population with multiple sclerosis [ 44 , 55 ], two were carried out on a population with Parkinson’s disease [ 11 , 20 ], three were carried out on people who were poststroke [ 12 , 18 , 37 ], one was carried out on a population with pulmonary fibrosis [ 25 ], and three were carried out on a population with lung cancer [ 14 , 26 , 45 ]. Six reviews focused on preoperatory preparation [ 24 ] and postoperatory preparation [ 31 , 33 , 52 , 56 ], and three reviews focused on the respiratory exercises for abdominal surgeries [ 17 , 50 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Respiratory muscle training (inspiratory and expiratory muscle training) and incentive spirometry improves respiratory muscle strength, peak expiratory flow (PEF), and pulmonary function [ 11 , 18 , 25 , 28 , 37 , 38 , 40 , 44 , 46 , 48 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IMT is one of the methods used to increase the respiratory muscle strength [30]. Pozuelo-Carrascosa et al [22] reported that respiratory muscle strengthening was effective in improving the lung function parameters, exhalation and inhalation muscle strength, and walking ability in patients after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of patients with stroke, respiratory rehabilitation is necessary for the inhalation muscles because the more difficult it is for a patient to walk, the worse the effect on inhalation muscles is [ 7 , 8 ]. Threshold inspiratory muscle training was used as a method to improve inspiratory function in stroke patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%